Fast and accurate identification by MALDI‐TOF of the zoonotic serovar E of Vibrio vulnificus linked to eel culture - Mirjam Boonstra; Belén Fouz; Betty van Gelderen; Inger Dalsgaard; Lone Madsen; Eva Jansson; Carmen Amaro; Olga Haenen (Journal of Fish Diseases, 2023)
Vibrio vulnificus is a zoonotic pathogen that can cause death by septicaemia in farmed fish (mainly eels) and humans. The zoonotic strains that have been isolated from diseased eels and humans after eel handling belong to clade E (or serovar E (SerE)), a clonal complex within the pathovar (pv.) piscis . The aim of this study was to evaluate the accuracy of MALDI‐TOF mass spectrometry (MS) in the identification of SerE, using the other two main pv. piscis ‐serovars (SerA and SerI) from eels as controls. MALDI‐TOF data were compared with known serologic and genetic data of five pv. piscis isolates or strains, and with the non pv. piscis reference strain. Based on multiple spectra analysis, we found serovar‐specific peaks that were of ~3098 Da and ~ 4045 Da for SerE, of ~3085 Da and ~ 4037 Da for SerA, and of ~3085 Da and ~ 4044 Da for SerI. Therefore, our results demonstrate that MALDI‐TOF can be used to identify SerE and could also help in the identification of the other serovars of the species. This means that zoonosis due to V. vulnificus could be prevented by using MALDI‐TOF, as action can be taken immediately after the isolation of a possible zoonotic V. vulnificus strain.